Enhancement under UV–visible and visible light of the ZnO photocatalytic activity for the antibiotic removal from aqueous media using Ce-doped Lu3Al5O12 nanoparticles. (October 2018) - Zammouri, Lobna; Aboulaich, Abdelhay; Capoen, Bruno; Bouazaoui, Mohamed; Sarakha, Mohamed; Stitou, Mostafa; Mahiou, Rachid
Graphical abstract: Abstract: We report the first synthesis of Ce-doped Lu3 Al5 O12 Nanoparticles/ZnO Nanostructure (LuAG:Ce/ZnO NS) via a rapid hydrolysis/condensation of Zn(OAc)2 on the surface of LuAG:Ce NPs. The structural, morphological and optical properties of LuAG:Ce/ZnO NS have been fully investigated using X-Ray Diffraction (XRD), Transmission Electron Microscopy (TEM), High Resolution Transmission Electron Microscopy (HRTEM), Energy Dispersive X-ray Spectroscopy (EDS), Fourier Transform Infrared Spectroscopy (FTIR), diffuse reflectance UV–visible spectroscopy and N2 adsorption/desorption measurements. Results showed that ZnO Nanocrystals (ZnO NCs) of about 10 nm diameter are homogeneously grown on the surface of 100 nm LuAG:Ce NPs in a core/shell-like structure. The photocatalytic activity of the as-prepared nanostructure has been evaluated throught the photodegradation of sulfathiazole (STZ), a molecule widely used as antibiotic, under UV–vis and visible light irradiation. Results showed that STZ undergoes much higher photodegradation in the presence of LuAG:Ce/ZnO NS compared to the pure ZnO NCs under both UV–vis and visible light. This enhanced photocatalytic capability was found to result from higher specific surface area and visible light absorption in LuAG:Ce/ZnO NS, which allowed for more surface active sites and enhanced hydroxyl radicals (˙OH) production from the nanostructured photocatalyst. The recyclability of LuAG:Ce/ZnO NS was also demonstrated.